The Role of Firm Size in Moderating Factors Influencing Tax Avoidance - Eka Hissina; Adelina Citradewi (DIPONEGORO UNIVERSITY, 2026)
This study aims to analyze the effect of profitability, leverage, and sales growth on tax avoidance, as well as to examine the role of firm size as a moderating variable. The research was conducted on 53 energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2024 using a quantitative approach and descriptive method. The analytical techniques employed were multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of IBM SPSS Statistics version 30. The results indicate that profitability has a significant effect on tax avoidance, while leverage and sales growth show no significant effect. Furthermore, firm size does not moderate the relationship between profitability and sales growth with tax avoidance, but it is able to moderate the effect of leverage on tax avoidance.